2018
DOI: 10.3399/bjgpopen18x101597
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics in anaemia of chronic disease in general practice: a real-world retrospective cohort study

Abstract: Background: Limited research has been performed that focused on the diagnosis of the underlying cause of anaemia of chronic disease (ACD) in general practice or on prevalence data of the underlying causes of ACD in general practice, although this is one of the most common types of anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
12
3
Order By: Relevance
“…It has been suggested that AI is mediated by the effect of proinflammatory cytokines, such as interleukin (IL)-6, in turn stimulating production of hepcidin, resulting in a combination of decrease in erythrocyte survival, impaired production of erythrocytes and hypoferremia. 3,4 Based on the initial evidence gathered so far 5,9 and enhanced by the larger sample size of this study compared with previous studies, it is possible that the local and systemic inflammatory reactions elicited by presence of periodontitis act on the cascade leading to increased production of hepcidin and to reduced production and survival of erythrocytes. Initial evidence suggests that HB and HCT levels may further decrease short-term following intensive periodontal therapy, 21 in line with traumatic anemia following surgery.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It has been suggested that AI is mediated by the effect of proinflammatory cytokines, such as interleukin (IL)-6, in turn stimulating production of hepcidin, resulting in a combination of decrease in erythrocyte survival, impaired production of erythrocytes and hypoferremia. 3,4 Based on the initial evidence gathered so far 5,9 and enhanced by the larger sample size of this study compared with previous studies, it is possible that the local and systemic inflammatory reactions elicited by presence of periodontitis act on the cascade leading to increased production of hepcidin and to reduced production and survival of erythrocytes. Initial evidence suggests that HB and HCT levels may further decrease short-term following intensive periodontal therapy, 21 in line with traumatic anemia following surgery.…”
Section: Discussionmentioning
confidence: 86%
“…It is now emerging that also erythrocytes are affected by chronic inflammatory diseases. This phenomenon, named “anemia of inflammation” (AI) may be mediated by the effect of pro‐inflammatory cytokines, such as interleukin (IL)‐6, which promote production of hepcidin, resulting in higher iron trapping within macrophages and liver cells; alternative mechanisms may be reduced erythropoiesis and mildly shortened erythrocyte survival . Some studies have reported reductions in hemoglobin (HB) levels, mean corpuscular hemoglobin (MCH), circulating erythrocytes, and hematocrit (HCT) in both CP ‒ and AgP .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And how is the effect of the actual classification on this? This would be expected, based on the ‘anaemia of chronic inflammation’ mediated by the effects of high levels of IL-6 and as a consequence of hepcidin, resulting in higher iron trapping within macrophages and liver cells [ 13 ]. Reduced HCT may lead to fatigue and reduced wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation is also associated with effects on red blood cells, possibly mediated by the effect of IL-6 and hepcidin and/or by reduced erythropoiesis. This phenomenon has been named ‘anaemia of chronic inflammation’ since it tends to occur in chronic inflammatory conditions [ 13 ]. In fact, reductions in haemoglobin levels, circulating red blood cells, haematocrit and mean corpuscular haemoglobin are suspected to be associated with both aggressive and chronic periodontitis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%